Relationship between Continuum of Hurst Exponents of Noise-like Time Series and the Cantor Set - Maria C. Mariani (MDPI AG, 2021)
In this paper, we have modified the Detrended Fluctuation Analysis (DFA) using the ternary Cantor set. We propose a modification of the DFA algorithm, Cantor DFA (CDFA), which uses the Cantor set theory of base 3 as a scale for segment sizes in the DFA algorithm. An investigation of the phenomena generated from the proof using real-world time series based on the theory of the Cantor set is also conducted. This new approach helps reduce the overestimation problem of the Hurst exponent of DFA by comparing it with its inverse relationship with <semantics>α</semantics> of the Truncated Lévy Flight (TLF). CDFA is also able to correctly predict the memory behavior of time series.